The Role of Service Quality, Satisfaction, and Value Perception in Increase Visitor Interest Study on Dental Poly Services UPT Semanu II Health Center - Erla Asmalasari; M Syamsu Hidayat; Surahma Asti Mulasari (Publikasi Indonesia, 2024)
Introduction : Patients who receive quality service, feel very satisfied or happy and receive the expected value, will make repeat visits to health services. Semanu II Health Center in Gunungkidul Yogyakarta during 2019-2022 experienced a decrease in patient return visits. Objective : The purpose of the study was to determine the effect of service quality, visitor satisfaction and perceived value both partially and simultaneously on the intention to revisit visitors at the Semanu II. Research Method : The research method used is a quantitative research method The population in the study was all visitors to the dental clinic who had visited the Semanu II Health Center in Yogyakarta, totaling 3,358 visitors. The sampling technique used accidental sampling. The number of samples was 97 visitors with the provision of using the Slovin formula. The technical data collection questionnaire will be carried out after visitors or patients are examined. The service staff will provide a questionnaire sheet to visitors or patients after they have been examined. Result : The results of the research are that there is an influence of service quality, satisfaction and perceived value on visitors interest in repeat visits, that service quality, satisfaction and perceived value partially and simultaneously had a significant positive effect on the intention to revisit. The ranking results found that the influence of satisfaction was more dominant than the influence of service quality and perceived value on the intention to revisit. Conclusion : Service quality, satisfaction, Perceived value simultaneously positive effect on visitor interest in repeat visits.